2018
DOI: 10.1523/jneurosci.3336-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Neural Computations Underlying Causal Structure Learning

Abstract: Behavioral evidence suggests that beliefs about causal structure constrain associative learning, determining which stimuli can enter into association, as well as the functional form of that association. Bayesian learning theory provides one mechanism by which structural beliefs can be acquired from experience, but the neural basis of this mechanism is poorly understood. We studied this question with a combination of behavioral, computational, and neuroimaging techniques. Male and female human subjects learned … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 63 publications
5
43
0
Order By: Relevance
“…We followed the same protocol as described previously (Tomov et al, 2018). Scanning was carried out on a 3T Siemens Magnetom Prisma MRI scanner with the vendor 32-channel head coil (Siemens Healthcare, Erlangen, Germany) at the Harvard University Center for Brain Science Neuroimaging.…”
Section: Methodsmentioning
confidence: 99%
“…We followed the same protocol as described previously (Tomov et al, 2018). Scanning was carried out on a 3T Siemens Magnetom Prisma MRI scanner with the vendor 32-channel head coil (Siemens Healthcare, Erlangen, Germany) at the Harvard University Center for Brain Science Neuroimaging.…”
Section: Methodsmentioning
confidence: 99%
“…model-free control was determined by Bayesian arbitration, but they did not address Pavlovian-instrumental interactions. A number of earlier theories argued that certain reinforcement learning behaviors could be understood as arising from a model comparison process [23][24][25][26] . However, to our knowledge, ours is the first account that directly addresses Pavlovian-instrumental interactions in terms of model comparison/averaging.…”
Section: Variancementioning
confidence: 99%
“…Indeed, these studies found that the degree of evidence of hierarchical structure using a Bayesian mixture of experts, akin to our meta-generalization agent, was related to the development of hierarchical gating policy in the neural network (Collins & Frank, 2013;. More recent work has suggested this form of structure learning is neurally dissociable from the associative learning and involves the rostrolateral prefrontal cortex and angular gyrus (Tomov et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…These models assume each context acts as a pointer to a latent structure, and generalizing task statistics requires inference over which structure the current context belongs to. This form of Bayesian non-parametric clustering and generalization can be approximately implemented in corticostriatal gating networks endowed with hierarchical structure (Collins & Frank, 2013) and have been used to explain human generalization behavior and neural correlates thereof in a number of reinforcement learning tasks Collins, 2017;Collins, Cavanagh, & Frank, 2014;Collins & Frank, 2013, 2016Schulz, Franklin, & Gershman, 2018;Tomov, Dorfman, & Gershman, 2018).…”
Section: Introductionmentioning
confidence: 99%